2012
DOI: 10.1007/s12633-012-9119-x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Titanium, Zirconium and Tin on the Growth of Diatom Synedra Acus and Morphology of Its Silica Valves

Abstract: The effect of three Group IV metals (titanium, zirconium and tin) on the growth, morphology and chemical composition of the freshwater diatom Synedra acus subsp. radians (Kützing) Skabichevsky was studied and compared with germanium. The elements in their highest oxidation states were introduced into the culture medium in the form of hydroxides. Germanium was found to be toxic at ≥5 mol. % of the total Ge-Si content in the culture medium. In the presence of other elements, a slight decrease in the cell divisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 40 publications
1
37
0
Order By: Relevance
“…The germanium, titanium, zirconium and tin were all found to be taken up by the silicon deposition vesicle (SDV) whereas the germanium disturbed the biosilicification process, causing frustule aberrations. However, the Ti, Zr and Sn were found to inhibit the biosilicification process in this species [47]. With respect to Ge, the conclusions of Basharina et al are consistent with previous studies which also report the incorporation of Ge into the frustules and the resulting changes in morphology [42,43,48,49].…”
Section: Manipulation and Modeling Of Frustule Formation And Compositionsupporting
confidence: 86%
See 1 more Smart Citation
“…The germanium, titanium, zirconium and tin were all found to be taken up by the silicon deposition vesicle (SDV) whereas the germanium disturbed the biosilicification process, causing frustule aberrations. However, the Ti, Zr and Sn were found to inhibit the biosilicification process in this species [47]. With respect to Ge, the conclusions of Basharina et al are consistent with previous studies which also report the incorporation of Ge into the frustules and the resulting changes in morphology [42,43,48,49].…”
Section: Manipulation and Modeling Of Frustule Formation And Compositionsupporting
confidence: 86%
“…Basharina et al [47] studied the effect of the incorporation of group IV metals (titanium, germanium, zirconium and tin) into diatom biosilica and found that these metals are taken up concomitantly into the cells with Si(OH) 4 , in their hydroxyl form, but only germanium was incorporated in significant quantities within the biosilica. The germanium, titanium, zirconium and tin were all found to be taken up by the silicon deposition vesicle (SDV) whereas the germanium disturbed the biosilicification process, causing frustule aberrations.…”
Section: Manipulation and Modeling Of Frustule Formation And Compositionmentioning
confidence: 99%
“…Lithium (Li) can alter the length and form of flagella in Chlamydomonas reinhardtii [ 28 ] or affect the structure of polysaccharide sheath around Ankistrodesmus gracilis cells [ 29 ], and can also at various concentrations inhibit other microalgae strains [ 30 , 31 ]. Cultivation of diatom Synedra acus in the presence of germanium (Ge), titanium (Ti), zirconium (Zr) or tin (Sn) caused alterations in shape, size and mechanical strength of silica valves in Synedra frustules [ 32 ].…”
Section: Effect Of Metals On Microalgae: Growth Inhibition mentioning
confidence: 99%
“…TiO 2 (Jeffryes et al 2008 ; Lang et al 2013 ) and GeO 2 (Gale et al 2011 ) have been incorporated by bio-uptake or deposited on the frustules post-cleaning. GeO 2 has been shown to inhibit diatom growth (Shea and Chopin 2007 ) and to interfere with frustule synthesis (Basharina et al 2012 ). The uptake of other elements may be regulated as a function of concentrations, and there will be biological limits to the amount of a specific element that can be incorporated.…”
Section: Introductionmentioning
confidence: 99%